SENAM LANSIA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Herawati; Ifansyah, M. Noor; Diani, Noor (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
Getting old is the final phase in the human life cycle. At the elderly people, there is commonlydecreasing of anatomic and organs function. The decreasing function at the blood artery can alsocause hypertension. One of the factors that can influence the decrease of hypertension without drugsis regular light exercise such as the gym for old people. The objective of this research was to revealthe influence of the gym for old people to blood pressure decrease on elderly people withhypertension in Tresna Werdha Budi Sejahtera Social Residential, Martapura. The research designuses One-group pre-post test design and as many as 30 people was became the total sample from thepopulation of this research. Based on the test of data normality, the data was not normally distributedso that it was not fulfill the T paired test and that makes another alternative test called the wilcoxontest, p value is obtained in 0,023 (p < 0,05) means Ho rejected and Ha received. It could beconcluded that there was influence of the gym for elderly to decrease blood pressure on elderlypeople with hypertension in PSTW Budi Sejahtera, Martapura.